Hox-5.1 defines a homeobox-containing gene locus on mouse chromosome 2. - Featherstone, M S (1988)
We have isolated a murine homeobox-containing gene, Hox-5.1, by virtue of its relatedness to the Hox-1.4 gene. In situ hybridization to metaphase spreads mapped Hox-5.1 to band D of mouse chromosome 2. Sequence comparisons indicate that Hox-5.1 is the murine homolog of the human C13 homeobox-containing gene. Hox-5.1 also bears significant similarity to the Xenopus Xhox-1A homeobox-containing gene and the Drosophila deformed homeotic gene at N-terminal and homeobox regions. Hox-5.1 transcripts were detected in mouse embryos, in adult mouse testis, kidney, heart, and intestine, and in mouse embryonal carcinoma cells treated with retinoic acid. In situ hybridization to sections from whole mouse embryos revealed Hox-5.1 expression in spinal cord and prevertebrae.